2012
DOI: 10.1302/0301-620x.94b7.29115
|View full text |Cite
|
Sign up to set email alerts
|

Wear in alumina-on-alumina ceramic total hip replacements

Abstract: We analysed 54 alumina ceramic-on-ceramic bearings from total hip replacements retrieved at one centre after a mean duration of 3.5 years (0.2 to 10.6) in situ. These implants were obtained from 54 patients (16 men and 38 women) with a mean age of 67 years (33 to 88) who underwent revision for a variety of reasons. Posterior edge loading was found in the majority of these retrievals (32 out of 54). Anterosuperior edge loading occurred less often but produced a higher rate of wear. Stripe wear on the femoral he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 33 publications
4
50
0
Order By: Relevance
“…Posterior edge loading, which occurs in positions of flexion > 90° may be considered to be normal in CoC bearings, with no clinical consequences, and is frequently seen in retrieved CoC bearings. 26 Posterior edge loading may also occur in more conventional polyethylene articulations with head sizes equivalent to those described in our study. As these bearing couples will not generate noise it is not reported as a problem, and yet wear associated with posterior edge loading in conventional bearings may prove to be a more significant clinical problem than for CoC articulations.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Posterior edge loading, which occurs in positions of flexion > 90° may be considered to be normal in CoC bearings, with no clinical consequences, and is frequently seen in retrieved CoC bearings. 26 Posterior edge loading may also occur in more conventional polyethylene articulations with head sizes equivalent to those described in our study. As these bearing couples will not generate noise it is not reported as a problem, and yet wear associated with posterior edge loading in conventional bearings may prove to be a more significant clinical problem than for CoC articulations.…”
Section: Discussionsupporting
confidence: 52%
“…However, the optimum acetabular component position and the relationship between acetabular component position and wear is highly dependent on patient range of movement, so that the ideal acetabular component position may be different for each patient. 26 A retrieval analysis undertaken by Esposito et al 26 has shown the interaction between cup position and wear, and from this it has been suggested that the classic square 'safe zone' 27-30 of acetabular implant position does not apply to the CoC articulation. The study by Esposito et al 26 in conventionally sized bearings also highlighted that lower anteversion and lower inclination may lead to an increased chance of posterior edge loading.…”
Section: Discussionmentioning
confidence: 99%
“…Esposito et al (2011) investigated the stripe wear in alumina-on-alumina, ZTA-on-ZTA and ZTA-on-alumina articulations. They received 20 forte and 11 delta components with similar implantation times (14 ± 6mo and 15 ± 12mo respectively).…”
Section: Clinical Applications and Clinical Results Of Ztamentioning
confidence: 99%
“…Reasons for revision were varied, including one squeaking forte-forte component. They reported that the average volumetric wear was lower for delta bearings, with an average wear rate of 0.06 ± 0.10 mm 3 /year, compared to forte bearings, with an average wear rate of 0.96 ± 1.87 mm 3 /year (Esposito; et al, 2011). …”
Section: Clinical Applications and Clinical Results Of Ztamentioning
confidence: 99%
“…Squeaking is a multifactorial complication that has been extensively reported with CoC articulations [27][28][29][30]. Retrieval studies show that patient, surgical and implant design may all contribute to squeaking [9,27,31].…”
Section: Discussionmentioning
confidence: 99%